(untitled) (Third Sector Social Economic Review, 2025)
The purpose of this study is to examine the relationship between technostress and job satisfaction and to reveal whether perceived organizational support has a moderating role in this relationship. Data were obtained from 255 teachers working in secondary schools in Ankara through a survey. The relationships and effects between variables were determined by correlation and regression analyses, confirmatory factor analysis was applied to the scales, and reliability and validity tests were performed. In addition, the moderating role of perceived organizational support was examined with the SPSS Process Macro application. The findings revealed that technostress negatively affects job satisfaction and perceived organizational support has a moderating effect in the relationship between technostress and job satisfaction. In this context, the most original finding of the research that fills the gap in the literature is that perceived organizational support has a moderating effect on the relationship between technostress and job satisfaction.